Adversity Quotient and Resilient HR Culture:A Success Strategy for Organizations (International Journal of Scientific Research and Management (IJSRM), 2014)
Culture is made up of the values, beliefs, underlying assumptions, attitudes, and behaviors shared by a group of people. Culture is the behavior that results when a group arrives at a set of generally unspoken and unwritten rules for working together. Culture is like personality as in a person, the personality is made up of the values, beliefs, underlying assumptions, interests, experiences, upbringing and habits that create a person’s behavior. Organizations culture is made up of all of the life experiences that each employee brings to the workplace. Culture is particularly influenced by the organization’s founder, executives, and other managerial staff because of their role in decision making and strategic direction. Adversity Quotient predicts how well one withstand adversity, overcome it, and foresee who will be crushed who will exceed and fall short of their expectations in performance and potential and who gives up and prevails or AQ is simply a measure of how you respond to adversity. This Paper Aims to build employees AQ and explains how to frame a resilient HR culture in organizations as human beings are the key drivers to build success strategies.